Evaluating the influence of openings configuration on natural ventilation performance of residential units in Hong Kong - Gao, C.F.; Lee, W.L. (Building and environment, 2011)
Natural ventilation performance of a residential dwelling is affected by a combination of internal and external factors. External factors are often subject to constraints beyond the control of site planners and architects. Internal factors include the openings configuration, which site planners and architects are free to design the way they deem proper. However, little information is available in this regard. In this study, a case study was conducted by tracer-gas measurements at a carefully selected residential unit for Computational Fluid Dynamics (CFD) model validation. A hypothetical residential unit was formulated to represent the characteristics of typical residential units in Hong Kong. CFD simulations were performed based on the hypothetical unit to evaluate the influence of different openings configurations on natural ventilation performance using the mean age of air. Openings configuration is defined by many parameters. Among the three studied parameters, evaluation results indicate that natural ventilation performance of residential units was most affected by the relative position of the two window openings groups (i.e. bedroom windows and living room windows), followed by building orientation and doors positions. It was found that better natural ventilation performance could be achieved when the two openings groups were positioned in opposite directions or perpendicular to each other. The combined effect of the three parameters was evaluated. It was found that varying two parameters at the same time offered positive improvements in natural ventilation performance, but varying all three parameters did not result in any improvement because of the counter-effects of changes in doors positions.